2021
DOI: 10.3390/metabo11100699
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Pentose Phosphate Pathway for SARS-CoV-2 Therapy

Abstract: SARS-CoV-2 is causing the coronavirus disease 2019 (COVID-19) pandemic, for which effective pharmacological therapies are needed. SARS-CoV-2 induces a shift of the host cell metabolism towards glycolysis, and the glycolysis inhibitor 2-deoxy-d-glucose (2DG), which interferes with SARS-CoV-2 infection, is under development for the treatment of COVID-19 patients. The glycolytic pathway generates intermediates that supply the non-oxidative branch of the pentose phosphate pathway (PPP). In this study, the analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Likewise, the increased amount of the enzyme TALDO1 can be linked to increased activity of the pentose phosphate pathway, which supplies the virus with ribonucleotides, essential building blocks for its replication. In addition, an unbiased proteome analysis has previously demonstrated that the infection of Caco-2 cells with SARS-CoV-2 increases the expression of TALDO 1 ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the increased amount of the enzyme TALDO1 can be linked to increased activity of the pentose phosphate pathway, which supplies the virus with ribonucleotides, essential building blocks for its replication. In addition, an unbiased proteome analysis has previously demonstrated that the infection of Caco-2 cells with SARS-CoV-2 increases the expression of TALDO 1 ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic shift towards ATP production in the glycolytic pathway clearly, also influences other metabolic pathways, such as the pentose phosphate pathway (PPP). In these conditions, the non-oxidative phase of PPP is increased, in which glycolysis intermediates are converted into the ribose-5-phosphate required for the synthesis of the nucleic acids, which is necessary for the virus replication [25,26]. In addition, high levels of oxidized glutathione and a significant decrease in enzymes forming part of the cellular defense line against oxidative stress were found, including superoxide dismutase 1 (SOD1), glucose-6-phosphate dehydrogenase, and peroxiredoxin [27][28][29].…”
Section: Covid-19 and Rbcs Metabolismmentioning
confidence: 99%
“…Importantly, a previous study reported a significant increase in the levels of some intermediates of the glycolytic and pentose phosphate pathways in sera of COVID-19 positive patients 50 . Moreover, SARS-CoV-2 infection was found to be associated with changes in the regulation of the pentose phosphate pathway in both in vivo (Caco-2 cells) 51 and in vitro (ferret model) 52 studies. These findings provide evidence of potential metabolic pathways linking the gut microbes to the clinical manifestations of COVID-19.…”
Section: Genome Annotation Reveals Functional Differentiation Between...mentioning
confidence: 99%